EFFECTS OF FRICTION STIR SPOT WELDING PARAMETERS ON THE WELD FRACTURE LOAD OF HIGH DENSITY POLYETHYLENE SHEETS - (:unkn) unknown (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2012)
The effects of the different welding parameters (tool rotation speed, tool plunge depth, tool dwell time and delay time) on weld fracture load of friction stir spot welds of high density polyethylene sheets were studied. The properties of friction stir spot welds have been determined to be highly dependent on the welding parameters. The tool rotational speed, tool plunge depth and dwell time were determined to be very important in a joint formation and its weld fracture load. The tool delay time had a positive effect on weld fracture load. The tool plunge rate had a negligible effect on friction stir spot welding of polyethylene sheets
Keywords: welding of polyethylene; friction stir spot welding; friction stir spot welding of plastics; friction stir welding tool; STATIC STRENGTH; TOOL